Estudio de prefactibilidad para la instalación de una planta productora de hojuelas de avena fortificadas con cereales andinos - Castro de la Mata Miranda, Paula (2020)
This research work seeks to determine the technological, commercial and financial viability of the installation of a production plant for oat flakes fortified with Andean cereals.